Solution combustion catalysts for the water-gas shift reaction - Van Der Merwe, Marianne Werle (Department of Chemical Engineering, 2019)
In the context of a growing world population, more sustainable solutions for energy generation are required. Fuel cells supplied with hydrogen generated from fuel processing trains have emerged as a potential medium-term solution due to their improved efficiency and lower greenhouse gas-emissions. This study focuses on the development of a compact, efficient design for fuel processing trains. More specifically, reduction in the size of the largest component, the Water Gas-Shift (WGS) reactor, which could be achieved by an increase in the catalytic activity via alternative catalyst synthesis techniques. Solution combustion synthesis (SCS) is one such technique that could be used since it allows for the preparation of highly-dispersed Pt oxide particles on low surface area CeO2 with a reproducible metal loading and a defined Pt particle size. The aim of this study was to investigate the “conventional” impregnation approach of supports prepared via SCS versus the one-shot SCS approach (support and active metal prepared in one step) for the synthesis of 1 wt.% Pt/CeO2 catalysts for the WGS reaction using a reformate feed stream. It was hypothesized that the preferential formation of metallic Pt species supported on CeO2 can be achieved using a glycine-nitrate combustion system with excess glycine fuel (stoichiometric ratios of glycine to nitrate oxidants > 1) i.e. the Pt is reduced during the one-shot SCS approach. The catalysts were characterized by XRD, N2-physisorption, ICP-AES, TEM and XPS, and their activity towards the WGS reaction was evaluated with a synthetic reformate stream (50 % H2, 6.67 % CO, 6.67 % CO2, 33.3 % H2O, 3.36 % He). Initial characterization results of the catalysts prepared by the one-shot SCS approach confirmed the reproducible synthesis of Pt particles supported on nano-sized CeO2 with low surface areas. Furthermore, TEM and XPS results of the one-shot SCS prepared catalysts indicated that the Pt species were mainly present as Pt oxide particles on the surface of the CeO2 supports. However, for combustion systems with excess fuel, formation of some metallic Pt was observed together with the more prevalent Pt oxide particles. The catalysts prepared by the “conventional” impregnation approach had higher activities towards the WGS reaction than the one shot SCS catalysts. This was attributed to the smaller Pt particles achieved using this “conventional” synthesis approach (approximately 1 nm compared to 3 nm). One-shot SCS is a viable synthesis approach for the preparation of 1 wt.% Pt/CeO2 catalysts as this method allows for the preparation of highly-dispersed Pt oxide particles on low surface area CeO2 with a reproducible metal loading and a defined Pt particle size. However, the characterization results indicated that using a combustion system with excess fuel resulted in the preferential formation of Pt oxide phases as opposed to the desired metallic Pt phase, therefore refuting the hypothesis of this study. Nevertheless, it is recommended to repeat the synthesis of the 1 wt.% Pt/CeO2 catalysts in an inert atmosphere as this has shown to favour the formation of metallic species (Cross et al., 2014). This study was unsuccessful in preparing catalysts using a glycine-nitrate one-shot SCS system that were more active than the “conventionally” prepared catalysts. However, it is recommended that other fuel types, such as urea, also be investigated. These alternative fuel types could combine the good Pt dispersion achieved using the one-shot SCS approach with potentially smaller Pt particle sizes, thereby increasing the catalyst’s activity towards the WGS reaction (Vita et al., 2015a).